Nitrous oxide emissions in silvopastoral systems: Key driving variables and seasonality - Cardoso, Abmael da Silva [UNESP]; Alari, Fernando de Oliveira [UNESP]; de Andrade, Nomaiací [UNESP]; Nascimento, Tiago da Silva [UNESP]; van Cleef, Flavia de Oliveira Scarpino; Alves, Bruno José Rodrigues; Ruggieri, Ana Cláudia [UNESP]; Malheiros, Euclides Braga [UNESP] (Elsevier, 2022)
Silvopastoral systems are suggested to be important strategies for mitigating greenhouse gas emissions. However, little information is available on the effects of these systems on soil nitrous oxide (N2O) production. Expanding the knowledge of N2O emissions and the responses of key variables that drive N2O production are essential for understanding nitrogen loss. To quantify these factors in the silvopastoral system (Eucalyptus grandis × Megathyrsus maximus) and the monoculture (Megathyrsus maximus Guinea Massai grass), we conducted a 4-year field assessment. The experimental design was a completely randomized block with two factors: (1) monoculture (MONO) and silvopastoral systems with tree rows of 12 m (SP1) and 6 m (SP2), and (2) two seasons (rainy and dry), with 5 repetitions. Emissions were quantified using the closed static chamber methodology and gas chromatography analysis. In the wet summer, the silvopasture system differed from MONO, while in the dry winter, only the SP1 group differed from the monoculture; N2O emissions were higher during the rainy season. The MONO treatment revealed larger N2O fluxes in the first year of evaluation, whereas the silvopasture systems peaked in a later year. A significant positive Pearson correlation was found between N2O fluxes and soil moisture (r=0.89; P < 0.001) and soil temperature (r=0.76; P< 0.01). Our study showed that the effect of the silvopastoral system was season-dependent. N2O emissions increased over the years in silvopastoral systems, as opposed to the monoculture, and were driven by soil moisture and temperature.
Keywords: Greenhouse gas emission; mixed pasture; N loss; N2O driving variable; N2O seasonality